2009
DOI: 10.1007/s00415-009-5077-7
|View full text |Cite
|
Sign up to set email alerts
|

Scalp periarterial saline efficacy in migraine and relation to exploding and imploding headache

Abstract: We recently reported the possibility of blocking a migraine attack by prolonged compression of scalp arteries and by the injection of saline around them, suggesting a role of extracranial structures in migraine pain. This study attempts further characterisation of the effect of saline infiltration and the relationship of the response to headache characteristics. A total of 40 patients were examined for scalp artery tenderness (superficial temporal main trunk and frontal branch, and occipital) during migraine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…However, in this study, there was no difference in headache directionality in patients who reported the use of prophylactic medications compared with those who did not. Concerns have previously been raised regarding an individual patient's ability to adequately and consistently describe headache pain and its directionality . Our study supports these concerns and suggests the need for further development and study of methods to assign migraine pain directionality.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…However, in this study, there was no difference in headache directionality in patients who reported the use of prophylactic medications compared with those who did not. Concerns have previously been raised regarding an individual patient's ability to adequately and consistently describe headache pain and its directionality . Our study supports these concerns and suggests the need for further development and study of methods to assign migraine pain directionality.…”
Section: Discussionsupporting
confidence: 75%
“…Concerns have previously been raised regarding an individual patient's ability to adequately and consistently describe headache pain and its directionality. 6,10 Our study supports these concerns and suggests the need for further development and study of methods to assign migraine pain directionality.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations